Chimeric Antigen Receptor T-Cell Therapy in Paediatric B-Cell Precursor Acute Lymphoblastic Leukaemia: Curative Treatment Option or Bridge to Transplant? - Buechner, Jochen; Caruana, Ignazio; Künkele, Annette; Rives, Susana; Vettenranta, Kim; Bader, Peter; Peters, Christina; Baruchel, André; Calkoen, Friso G. (Frontiers in Pediatrics, 2022)
Chimeric antigen receptor T-cell therapy (CAR-T) targeting CD19 has been associated with remarkable responses in paediatric patients and adolescents and young adults (AYA) with relapsed/refractory (R/R) B-cell precursor acute lymphoblastic leukaemia (BCP-ALL). Tisagenlecleucel, the first approved CD19 CAR-T, has become a viable treatment option for paediatric patients and AYAs with BCP-ALL relapsing repeatedly or after haematopoietic stem cell transplantation (HSCT). Based on the chimeric antigen receptor molecular design and the presence of a 4-1BB costimulatory domain, tisagenlecleucel can persist for a long time and thereby provide sustained leukaemia control. ‘Real-world’ experience with tisagenlecleucel confirms the safety and efficacy profile observed in the pivotal registration trial. Recent guidelines for the recognition, management and prevention of the two most common adverse events related to CAR-T – cytokine release syndrome and immune-cell–associated neurotoxicity syndrome – have helped to further decrease treatment toxicity. Consequently, the questions of how and for whom CD19 CAR-T could substitute HSCT in BCP-ALL are inevitable. Currently, 40–50% of R/R BCP-ALL patients relapse post CD19 CAR-T with either CD19- or CD19+ disease, and consolidative HSCT has been proposed to avoid disease recurrence. Contrarily, CD19 CAR-T is currently being investigated in the upfront treatment of high-risk BCP-ALL with an aim to avoid allogeneic HSCT and associated treatment-related morbidity, mortality and late effects. To improve survival and decrease long-term side effects in children with BCP-ALL, it is important to define parameters predicting the success or failure of CAR-T, allowing the careful selection of candidates in need of HSCT consolidation. In this review, we describe the current clinical evidence on CAR-T in BCP-ALL and discuss factors associated with response to or failure of this therapy: product specifications, patient- and disease-related factors and the impact of additional therapies given before (e.g., blinatumomab and inotuzumab ozogamicin) or after infusion (e.g., CAR-T re-infusion and/or checkpoint inhibition). We discuss where to position CAR-T in the treatment of BCP-ALL and present considerations for the design of supportive trials for the different phases of disease. Finally, we elaborate on clinical settings in which CAR-T might indeed replace HSCT.